Decreased prefrontal functional brain response during memory testing in women with Cushing's syndrome in remission. (August 2017) - Ragnarsson, Oskar; Stomby, Andreas; Dahlqvist, Per; Evang, Johan A.; Ryberg, Mats; Olsson, Tommy; Bollerslev, Jens; Nyberg, Lars; Johannsson, Gudmundur
Highlights: Women with Cushing's syndrome in remission have decreased functional brain response during episodic and working memory testing. The most prominent differences between patients and controls were found in the prefrontal cortex, a key region for cognitive function. A trend for decreased functional brain response was seen in the hippocampus during episodic memory encoding. These findings illustrates the long-term adverse effects of hypercortisolaemia on brain function. Abstract: Neurocognitive dysfunction is an important feature of Cushing's syndrome (CS). Our hypothesis was that patients with CS in remission have decreased functional brain responses in the prefrontal cortex and hippocampus during memory testing. In this cross-sectional study we included 19 women previously treated for CS and 19 controls matched for age, gender, and education. The median remission time was 7 (IQR 6–10) years. Brain activity was studied with functional magnetic resonance imaging during episodic- and working-memory tasks. The primary regions of interest were the prefrontal cortex and the hippocampus. A voxel-wise comparison of functional brain responses in patients and controls was performed. During episodic-memory encoding, patients displayed lower functional brain responses in the left and right prefrontal gyrus (p < 0.001) and in the right inferior occipital gyrus (p < 0.001) compared with controls. There was a trend towards lower functional brain responses in the left posterior hippocampus in patients (p = 0.05). During episodic-memory retrieval, the patients displayed lower functional brain responses in several brain areas with the most predominant difference in the right prefrontal cortex (p < 0.001). During the working memory task, patients had lower response in the prefrontal cortices bilaterally (p < 0.005). Patients, but not controls, had lower functional brain response during a more complex working memory task compared with a simpler one. In conclusion, women with CS in long-term remission have reduced functional brain responses during episodic and working memory testing. This observation extends previous findings showing long-term adverse effects of severe hypercortisolaemia on brain function.